Pengembangan Bahan Ajar Berbasis Komik Dengan Pendekatan Culturally Responsive Teaching Terhadap Literasi Siswa Pada Mata Pelajaran IPAS Kelas V SD - Retno Juliati Juli; Nurul Fitriah Aras; Sinta Satria Dewi Pendit (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2026)
This study aims to develop comic-based teaching materials using a Culturally Responsive Teaching (CRT) approach to improve students’ scientific literacy in Science and Social Studies (IPAS) learning for fifth-grade students at SD Inpres 3 Kotaraya. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were fifth-grade students and their classroom teacher. Data were collected through observation, interviews, validation questionnaires, practicality questionnaires, and pretest-posttest assessments. The results showed that the developed comic-based teaching materials were categorized as very valid, with a material expert validation score of 95.3% and a media expert validation score of 88%. The practicality test indicated very positive responses from students (93,96%) and teachers (94.8%). The effectiveness test showed a significant improvement in students’ scientific literacy, with the average score increasing from 56% (pretest) to 88% (posttest), and an N-Gain score of 0.727 (high category). Therefore, comic-based teaching materials integrated with CRT are feasible, practical, and effective in improving students’ scientific literacy in IPAS learning.